Psychoanalytic Exploration of Momma's Post-Traumatic Stress Disorder and Defense Mechanisms in Never Let Go - Nisa, Clarissa Adaira; Nirmalawati, Widya (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores Post-Traumatic Stress Disorder (PTSD) as portrayed in the character of Momma, the main character in Never Let Go (2024), and her use of defense mechanisms to cope with her past trauma. Using a descriptive qualitative approach, through Bessel Van Der Kolk's trauma theory and Sigmund Freud's concept of defense mechanisms, this study reveals Momma's extreme measures in isolating her children and enforcing strict rules by avoiding “The Devil” as a result of her grief and fear of loss. Data was collected from scenes, dialogues, and visual components, focusing on Momma's overprotective behavior towards her children. The researcher found several components of Post-Traumatic Stress Disorder symptoms, namely intrusive memories, avoidance, emotional numbness, and hyperarousal. At the same time, three characteristics of defense mechanisms are reflected in Momma, namely projection, denial, and displacement. This research shows the relevance of trauma shaping patterns of behavior, especially in a mother, as well as the relationship between psychological trauma, especially the body's response to traumatic experiences, the maternal relationship, and excessive parenting behavior.